Β‐Strand Mimetic Foldamers Rigidified through Dipolar Repulsion1. (19th January 2015) - German, Elizabeth A.; Ross, Jonathan E.; Knipe, Peter C.; Don, Michaela F.; Thompson, Sam; Hamilton, Andrew D.
Abstract Many therapeutically relevant protein–protein interactions contain hot‐spot regions on secondary structural elements, which contribute disproportionately to binding enthalpy. Mimicry of such α‐helical regions has met with considerable success, however the analogous approach for the β‐strand has received less attention. Presented herein is a foldamer for strand mimicry in which dipolar repulsion is a central determinant of conformation. Computation as well as solution‐ and solid‐phase data are consistent with an ensemble weighted almost exclusively in favor of the desired conformation.